The interplay between DNA methylation and cardiac autonomic system functioning: a systematic review. - Dos Santos Oliveira, Nayara Cristina; Serpeloni, Fernanda; Gonçalves de Assis, Simone (International Journal of Environmental Health Research, 2023)
Epigenetic marks, particularly DNA methylation (DNAm), are emerging as an important biological marker of susceptibility to cardiac autonomic dysfunction. This review summarizes recent discoveries about the association between DNAm and cardiac autonomic activity. A systematic literature search was performed through the Embase, Web of Science, Cochrane Library, Pubmed, PsycINFO, and Pilots databases. Twenty-two studies met inclusion criteria, of which 18 were human studies including a total of 2,686 participants. DNAm differences in multiple genes, such as NR3C1, TLR2, GPR133, EPO, PHGDH, OXTR, and SLC7A11, linked environmental stressors to physiological responses. For instance, exposure to psychosocial stressors increased NR3C1 methylation, which was associated with both decreased blood pressure and increased parasympathetic activity. Additionally, GPR133 played a potential role in cardiac autonomic dysfunction in an occupational setting, affecting the heart rate's deceleration capacity in welders. This review's findings suggest that DNAm is involved in cardiac autonomic regulation under different stress-mediated responses.